Low-Molecular-Weight Heparin Enhanced Therapeutic Effects of Human Adipose-Derived Stem Cell Administration in a Mouse Model of Lupus Nephritis - Matsuda, Shogo; Kotani, Takuya; Saito, Takashi; Suzuka, Takayasu; Mori, Tatsuhiko; Takeuchi, Tohru (Frontiers in Immunology, 2022)
Background: Lupus nephritis is a life-threatening complication in systemic lupus erythematosus (SLE), but the efficiency of current therapies involving corticosteroids, immunosuppressants, and biological agents is limited. Adipose-derived mesenchymal stem cells (ASCs) are gaining attention as a novel treatment for inflammation in SLE. Low-molecular-weight heparin (LMWH) exhibits multiple functions including anti-inflammatory, anti-fibrotic, and cell function-promoting effects. LMWH stimulation is expected to increase the therapeutic effect of ASCs by promoting cellular functions. In this study, we investigated the effects of LMWH on ASC functions and the therapeutic effect of LMWH-activated human-ASCs (hep-hASCs) in an SLE mouse model. Methods: The cellular functions of human-derived ASCs stimulated with different LMWH concentrations were observed, and the optimum LMWH dose was selected. The mice were assigned to control, human-ASC, and hep-hASC groups; treatments were performed on week 20. Twenty-six week-old mice were sacrificed, and urine protein score, serum blood urea nitrogen, creatinine (Cr), anti-ds DNA IgG antibody, and serum IL-6 levels were analyzed in each group. Mice kidneys were evaluated via histological examination, immunohistochemical staining, and gene expression levels. Results: LMWH significantly promoted ASC migration and proliferation and hepatocyte growth factor production and upregulated immunomodulatory factors in vitro. Hep-hASC administration resulted in significant disease activity improvement including proteinuria, serum Cr and IL-6 levels, anti-ds DNA IgG antibody, glomerulonephritis, and immune complex in mice. Inflammation and fibrosis in kidneys was significantly suppressed in the hep-hASC group; the gene expression levels of TNF-alpha, TIMP-2, and MMP-2 was significantly downregulated in the hep-hASC group compared with the control group. Conclusions: Hep-hASC exhibited higher anti-inflammatory and anti-fibrotic effects than hASCs and may be a candidate tool for SLE treatment in future.